2015
DOI: 10.1371/journal.ppat.1004620
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Oncogene Expression in T-DNA-Transformed Host Plant Cells

Abstract: Virulent Agrobacterium tumefaciens strains integrate their T-DNA into the plant genome where the encoded agrobacterial oncogenes are expressed and cause crown gall disease. Essential for crown gall development are IaaH (indole-3-acetamide hydrolase), IaaM (tryptophan monooxygenase) and Ipt (isopentenyl transferase), which encode enzymes for the biosynthesis of auxin (IaaH, IaaM) and cytokinin (Ipt). Although these oncogenes are well studied as the tumor-inducing principle, nothing is known about the regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…Infecting plant cells by Agrobacterium involves transferring T‐DNA from the bacteria to the plant cell nucleus and integrating it into the plant genome . Oncogenes such as ipt (isopentenyl transferase), iaaM (tryptophan monooxygenase) and iaaH (indole‐3‐acetamide hydrolase) are found in the T‐DNA, and their expression is responsible for the overproduction of cytokines and auxins, resulting in the initiation of uncontrolled cell division and growth and producing a tumour …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infecting plant cells by Agrobacterium involves transferring T‐DNA from the bacteria to the plant cell nucleus and integrating it into the plant genome . Oncogenes such as ipt (isopentenyl transferase), iaaM (tryptophan monooxygenase) and iaaH (indole‐3‐acetamide hydrolase) are found in the T‐DNA, and their expression is responsible for the overproduction of cytokines and auxins, resulting in the initiation of uncontrolled cell division and growth and producing a tumour …”
Section: Introductionmentioning
confidence: 99%
“…11 Oncogenes such as ipt (isopentenyl transferase), iaaM (tryptophan monooxygenase) and iaaH (indole-3-acetamide hydrolase) are found in the T-DNA, and their expression is responsible for the overproduction of cytokines and auxins, resulting in the initiation of uncontrolled cell division and growth and producing a tumour. 12 Different biotechnological approaches have been developed to control crown gall disease. For example, truncated genes involved in T-DNA transfer have been used in transformation experiments to induce resistance to crown gall.…”
Section: Introductionmentioning
confidence: 99%
“… Ditt et al (2006) reported no difference in gene expression between Agrobacterium -infected and mock-infected Arabidopsis at 4–24 h post-infection (hpi), although their microarray analysis did reveal distinct sets of up-regulated defense genes, as well as down-regulated cell-proliferation genes, at 48 hpi. In contrast, other studies (e.g., Veena et al, 2003 ; Lee et al, 2009 ; Zhang et al, 2015 ) uncovered a variety of alterations in the host transcriptome at earlier time points. Given the rapidity of the basal defenses described here, it seems likely that Ditt et al (2006) missed many of the changes in gene expression that may well have returned to pre-infection levels by 4 hpi.…”
Section: Pathogen Elicitors and Host Recognition/response Systemsmentioning
confidence: 79%
“…The three major Agrobacterium -derived cancer-causing transgenes encode enzymes that direct the production of the phytohormones auxin and cytokinin ( Lacroix and Citovsky, 2013a ). Zhang et al (2015) discovered that although the auxin-production genes IaaH and IaaM are constitutively expressed in Arabidopsis , the promoter for the cytokinin synthesis gene Ipt contains several W-boxes and is activated by the mutually interacting trio of WRKY18, WRKY40 and WRKY60. WRKY40 and WRKY60 are induced within 2 h of Agrobacterium infection, while WRKY18 is turned on slightly later.…”
Section: Pathogen Elicitors and Host Recognition/response Systemsmentioning
confidence: 99%
See 1 more Smart Citation